Analisis Kualitas Internal dan Eksternal Pendidkan Islam - Nanda Miranda (Yayasan Rahmat Islamiyah, 2021)
The quality of education is a concern of various circles, both the education community and the community. Each educational institution has its own advantages so that it can provide the best satisfaction for students, parents and the community. Internal quality includes students, parents, teachers and administrative staff who are in the education system. The external quality of education includes the industrial community, institutions or agencies that are outside the organization. The quality assurance system for primary and secondary education consists of two components, namely the internal quality assurance system (SPMI) and the external quality assurance system (SPME). School Self-Evaluation (EDS) is an internal self-evaluation process based on the National Education Standards (SNP) used. As the basis for the preparation of the RKS. The external quality assurance cycle can be divided into three groups according to the focus of tasks and authorities according to the quality improvement, quality development and accreditation facilities.